INTERLABORATORY STUDY: DEUTERIUM OXIDE ENRICHMENT ANALYSIS OF WATER SAMPLES USING PORTABLE FOURIER TRANSFORM INFRARED SPECTROPHOTOMETRY - Urteaga, Noelia; Muñoz Vera, Maruska; San Miguel Simbrón, José Luis (TECCIENCIA, 2023)
Analysis of body composition and consumption of breast milk using stable isotopes are highly accurate through standardized and non-invasive techniques. Laboratories around the world participate in inter laboratory studies to verify their performance in analysis of water samples enriched with deuterium. The goal of this study is to evaluate the results of the first inter-laboratory study for the analysis of water samples enriched with deuterium oxide in portable Fourier Transform Infrared spectrophotometry equipment of laboratories included in Technical Cooperation programs from International Atomic Energy Agency of which Bolivia is part. This descriptive cross-sectional study was carried out in countries around the world. Four standardized samples of water enriched with deuterium oxide in the range of 0 to approximately 1000 parts per million (mg/kg) above the natural abundance of the source water which is approximately 150 parts per million (ppm); the enrichment analysis was carried out between 2019 and 2020 and data was obtained from the official report. A total of 41 laboratory reports have been received, only 27 reports correspond to laboratories equipped with portable FTIR, the distribution of the enrichment averages show a similar distribution between the laboratories and the intra-laboratory variability found in the portable equipment is less than the global variability. Regarding the acceptability criteria we found 3 laboratories with results out of the acceptability range. In conclusion, most of the laboratories show acceptable performance results, the local laboratory has met the criteria set by the inter-laboratory study.